2022
DOI: 10.1021/acs.est.1c08011
|View full text |Cite
|
Sign up to set email alerts
|

Current Methods and Prospects for Analysis and Characterization of Nanomaterials in the Environment

Abstract: Analysis and characterization of naturally occurring and engineered nanomaterials in the environment are critical for understanding their environmental behaviors and defining real exposure scenarios for environmental risk assessment. However, this is challenging primarily due to the low concentration, structural heterogeneity, and dynamic transformation of nanomaterials in complex environmental matrices. In this critical review, we first summarize sample pretreatment methods developed for separation and precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 289 publications
(499 reference statements)
0
19
0
Order By: Relevance
“…We used the mealworm frass at the end of the 6-week experiment for analysis because the mealworms have reached the stabilization phase of PS and PE biodegradation since Week 4. After the supernatant became clear, the solution containing residual plastic particles was allowed to stand for 1 h. ,, The solution containing residual plastic particles underwent filtration using a polyamide (PA) membrane filter (porosity: 100 nm, Yibo Filter Material Co., Zhejiang, China), which was the most suitable filter with the smallest available pore size. The micro- and submicroplastic particles with a size exceeding 100 nm on the filter membrane were meticulously collected and observed under high vacuum conditions using a scanning electron microscope (SEM; Phenom Pro, Phenom World Inc., Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…We used the mealworm frass at the end of the 6-week experiment for analysis because the mealworms have reached the stabilization phase of PS and PE biodegradation since Week 4. After the supernatant became clear, the solution containing residual plastic particles was allowed to stand for 1 h. ,, The solution containing residual plastic particles underwent filtration using a polyamide (PA) membrane filter (porosity: 100 nm, Yibo Filter Material Co., Zhejiang, China), which was the most suitable filter with the smallest available pore size. The micro- and submicroplastic particles with a size exceeding 100 nm on the filter membrane were meticulously collected and observed under high vacuum conditions using a scanning electron microscope (SEM; Phenom Pro, Phenom World Inc., Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…A review (291 references) on the characterisation of nanomaterials in the environment covered, 57 amongst other topics, the preconcentration of nanomaterials from aqueous samples, their quantification by sp-ICP-MS and XRFS and their characterisation by techniques such as FFF-ICP-MS and LA-ICP-MS. A more specific review (74 references) on the trends and challenges in determining engineered NPs in seawater drew 58 the reader’s attention to the important fact that the main limitation of many studies is the use of spiked samples at concentrations much higher than those found in real samples. Of note was the table on atomic spectrometric methods used and the sample preparation procedures required prior to analysis.…”
Section: Water Analysismentioning
confidence: 99%
“…Nanoparticles were the topic of a comprehensive review (290 references) that covered 57 advances in methods for determination of their abundance, morphology, composition and structure in water, soil, sediment and biological samples. Laser- and plasma-based approaches for NP characterisation were included 117 in a broader review (596 references) that also covered monitoring of NP synthesis and the use of NPs for signal enhancement.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterisation of the physico-chemical properties of nanoparticles requires application of various methods, such as microscopic, spectroscopic, mass spectrometric, and sizefractionation, which provide complementary information about nanoparticles. 5,6 Among them, inductively coupled plasma-mass spectrometry (ICP-MS) has sufficiently low detection limits and selectivity for the analysis of trace levels of metallic nanoparticles in complex environmental and biological samples. However, this requires operation of ICP-MS in single particle mode or in combination with a separation technique, such as eld ow fractionation (FFF), capillary electrophoresis (CE) or high performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%